Analisis Penggunaan Sistem Informasi Manajemen Bidang Kurikulum Di SMA PGII 1 Bandung - Widia Yusuf`, Ilham Agustian; Hafidh, Zaini (Universitas Pendidikan Indonesia, 2024)
The growing technological advances have an impact on the field of education, one of which is the education curriculum. In utilizing technological developments, schools to integrate curriculum management can use Management Information Systems (MIS) to facilitate management. In addition, this study has the aim of further discussing the use of Management Information Systems (MIS) in the field of curriculum at PGII senior high school 1 Bandung. A qualitative approach is used in this research with a case study method, the type of data used is qualitative data and there is also quantitative data as complementary data. The data collection techniques used are interview techniques, observation, and analyzing documents. Another purpose of this research is to find out how schools conceptualize information system design and how to operate information systems, planning information systems in the curriculum field, implementing the use of information systems in the curriculum field, and evaluating the use of information systems in the curriculum field. Based on the results of the research, the implementation of the Management Information System (MIS) in the curriculum field is running well, although the implementation of the platform used needs to be re-optimized.